PERBEDAAN TINGKAT PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT SISWA SDN 2 SINGAPADU KALER SEBELUM DAN SESUDAH DILAKUKAN PENYULUHAN - I Nyoman Wirata; Anak Agung gede Agung (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2016)
8.5 % of the Gianyar regency population have the teeth and mouth problem. The knowledge of oral health care needs to be improved. The Oral health is a fundamental part of public health and well-being .The purpose of this study is to know the differences of oral health care knowledge level of SDN 2 Singapadu Kaler students before and after given education. The total population of this experimental sudy were 40 students. Data was based on the answers of the questionnaire before and after given education.The results of this study showed that the oral health care knowledge level of SDN 2 Singapadu Kaler students before and after given education were different significantly (p0.05). The mean of knowledge level after given education had changed from 63.87 to 91. Conclusion of this study is the oral health care knowledge level of SDN 2 Singapadu Kaler students after given education has increased.